Teacher’s perspective on diagnostic assessment process during the pandemic Covid-19 - Yusron, Eri; Istiyono, Edi; Hidayati, Kana; Retnawati, Heri; Hassan, Aminuddin; Ummul Karimah (Pegem Akademi Yayincilik, 2024)
Diagnostic assessment is an assessment process that aims to diagnose students’ abilities and make learning improvements during the pandemic. The study aims to explore the assessment process during a pandemic, provide an overview of the di-agnostic assessment process, and provide feedback on the results of the diagnosis assessment. This research was conducted with a qualitative approach using a phenomenological research design. This approach is considered appropriate to achieve phenomenal research objectives. The research subjects were 13 district and city elementary school teachers in the province of West Java. The selection of this location is determined by the value of the education index, which has increased in the last four years. The instruments used have been validated by experts and improved according to expert recommendations. (Focus Group Discussion) FGD is used to confirm the results of online learning observations. FGDs were conducted online with 13 teachers, and observations were made on five online learning processes. Data analysis using the Bogdan & Blinken model was carried out with the stages of data reduction, presenting data, making conclusions, and verifying results. Based on FCDs, there are differences in the assessment process between district and city schools in West Java during the pandem-ic. This is due to the disparity in the availability of facilities that can be provided by schools in districts and cities, affecting the pattern or way teachers assess learning. The challenges for teachers are coordination with parents and the difficulty of developing diagnostic assessment instruments. Furthermore, the diagnostic assessment has not provided good feedback for students because the diagnostic assessment has not been planned and structured. Future research is expected to discuss and develop diagnostic assessment instruments to help teachers conduct online diagnostic assessments that can be used even after the pandemic and for the longer term.